Assessment of nutritional status and preference of nutritional supplements among anganwadi children - E., Suganya; H. N., Vrushabhendra; S., Srikanth; V., Sudha (International Journal Of Community Medicine And Public Health, 2017)
Background: Integrated Child Development Scheme (ICDS) was launched in India during 1975, to tackle the high prevalence of malnutrition among under 5 children. NFHS 3 (2005-06) reports that only 33% of ICDS services were utilized by them. To ensure the effectiveness of the scheme, nutritional status of under 5 children and the form of nutritional supplement - either Hot Cooked Meals (HCM) or Take Home Ration (THR), preferred by the beneficiaries must be assessed. Methods: A Cross sectional study was done among under 5 children in 2015 for a period of 2 months, in three randomly selected villages, Rural Field Practice Area, Sri Venkateshwaraa Medical College Hospital & Research Centre, Puducherry. Weight and Height were measured for all the eligible children using standard procedures. World Health Organization (WHO) growth standards were used to assess their nutritional status. The mothers were enquired about the nutritional supplement utilization, type of nutrition supplement (HCM/THR) utilized by their children and the reasons for preference. Statistical significance was assessed by chi-square test. Results: Among 153 children enrolled, 138 (90%) were consuming HCM and 15 (10%) were THR utilizers. The overall prevalence of under nutrition was 59%. The prevalence of underweight, stunting and wasting were 28%, 28% and 38.5% respectively and it was found significantly (p value <0.05) higher among THR utilizers (74%, 60% and 53% respectively) than those receiving HCM (25%, 36% and 23%). Conclusions: HCM was preferred more than THR. The children receiving HCM were better nourished than THR utilizers.